The impact of China's economic power on the diffusion of Chinese language: a case study of the Malaysian language landscape / Choo Kim Fong - Choo, Kim Fong (Universiti Teknologi MARA, 2023)
The Chinese language in Malaysia has been preserved and passed on through the persistent efforts of the local Chinese, and it has become one of the few immigrant groups that have still managed to retain a complete native language education system and national language development. Although it is still able to achieve steady development, but it also faces challenges in the context of the government's implementation of a unitary development of language and education policies. With the rise of China's economic power, Malaysia maintains close economic ties with China, which has been Malaysia's largest trading country for more than a decade. The influence of China's economic strength has given the Chinese language a higher market value. This is undoubtedly a major external boost to the sustainable development of the Chinese language and Chinese language education for the local Chinese community.In the context of this study, the Malaysian linguistic landscape is used as a framework to examine whether the government and the general public's attitudes towards Chinese language and the status of Chinese language have changed due to China's economic development. It was found that the official government signage implemented the government regulations which only uses Malay as the official language, but the bilingual road signs demonstrated the government's inclusiveness and openness. Private shop signs are multilingual, with bilingual and trilingual signs being the most common. Private signs tend to use common languages like Malay, English and Chinese. The languages chosen are mainly due to their commercial value. The findings also found that the use of Chinese language is mainly limited to Chinese businesses, while non-Chinese businesses subjectively recognize the commercial value of Mandarin; they do not actually use it. As a result, the status of Mandarin in Malaysia has not been significantly improved.